The Influence Of Service Quality on Patient Satisfaction, Perception, Trust and Behavioral Intention at Santo Damian Hospital - Felicitas Budiawati; Simon Sia Niha; Jou Sewa Adrianus; Stanis Man; Yulius Yasinto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
This research explores the relationship between service quality, patient satisfaction, patient perception, and patient trust at Santo Damian Lembata Hospital, East Nusa Tenggara, and their impact on patient behavioral intentions. The study focuses on evaluating how service quality affects patient satisfaction, perception, and trust, and how these variables influence patient behavior. The research was conducted among outpatients at the hospital, using a sample of 115 individuals selected through accidental sampling based on 18 indicators. Service quality is the independent variable, while behavioral intention is the dependent variable. Data collection involved questionnaires, interviews, and secondary sources, and the analysis was performed using descriptive and inferential statistics, including Partial Least Square (PLS). The findings indicate that high service quality at Santo Damian Hospital positively affects patient satisfaction, perceptions, trust, and behavioral intentions. Furthermore, the study confirms that patient satisfaction, perception, and trust serve as mediators between service quality and patient behavioral intentions. This emphasizes the significance of these factors in shaping patient behavior within the hospital setting. The research underscores the crucial role of maintaining high service quality to enhance overall patient experiences and encourage positive behavioral outcomes.